The degree to which basic education teachers possess skills for employing artificial intelligence (AI) in education (Field study in the city of Tartous) (Journal of Hama University, 2025)
The research aimed to identify the degree to which basic education teachers possess the skills of employing artificial intelligence (AI) in education in the city of Tartous. The research sample consisted of (427) basic education teachers in the city of Tartous, according to the research variables (scientific qualification, teaching experience), To achieve the research goal, the researcher followed the descriptive analytical approach and used a questionnaire consisting of (35) items, which included (7) skills: (Lesson planning, lesson preparation, evaluation, interaction with students, classroom management, professional development and training, parent involvement) prepared by the researcher, after its validity and reliability were verified, and the results were as follows:- The degree to which basic education teachers have skills for employing artificial intelligence (AI) in education in the city of Tartous is weak, with an average arithmetic mean (2.30), and a standard deviation (0.557).- There are statistically significant differences at the significance level (0.05) between the average scores of teachers’ answers to the questionnaire on the skills of employing artificial intelligence (AI) in education according to the academic qualification variable, and in favor of postgraduate studies.- There are no statistically significant differences between the average scores of teachers’ answers to the questionnaire on the skills of employing artificial intelligence (AI) in education according to the variable of teaching experience.In light of the findings, the current research suggested the need to organize intensive training programs covering various aspects of artificial intelligence in education, including data analysis, content customization, performance evaluation, and providing continuous technical support to teachers to help them overcome technical challenges
Keywords: artificial intelligence, Skills for employing artificial intelligence in education.